EFECTO DE LA INOCULACIÓN DE ACTINOBACTERIAS COMO PGPR EN PLANTAS DE PIMIENTO (Capsicum annuum) - Sierra Arriaga, Lady Michelle (2023)
The use of more ecological and efficient alternatives to synthetic fertilizers is increasingly required, actinobacteria have the ability to function as biostimulants for the growth and development of bell pepper plants under nursery conditions. Under this principle, the objective of this research was to evaluate the effect of actinobacteria inoculation on bell pepper (Capsicum annuum) plants. The research was carried out in the facilities of the Experimental Campus "La María" under controlled conditions.